From Rescue to Rebirth: Portugal and Italy’s Government Strategies for National Airlines Amidst COVID-19 - Madeira, M. (27th ATRS World Conference, 2024)
Due to COVID-19, several Governments in Europe were called in to help their struggling airlines surpass this patch of rough air. Two cases stand out in the European context: TAP Air Portugal and Alitalia, both renowned Southern European state-owned flag carriers with a long history of financial difficulties and political meddling. However, the government intervention in these two similar cases unfolded in opposite fashions. In the Portuguese case, the Government performed a 3.2 billion Euro injection and increased its stake in the company from 51 to 100%, preventing its collapse. In the Italian case, however, the Government decided that Alitalia was beyond salvation and created a new airline - ITA Airways - by buying some assets of Alitalia and drawing to a close the operations of the latter. Using the Multiple Streams Framework (MSF), this paper tries to shed some light on the processes by which these two cases ended up with the aforementioned outcomes as a result of their respective government interventions during the same policy window – the COVID-19 pandemic. By doing so, it hopes to contribute to the discussion of the processes behind Government interventions in ailing state-owned airlines during crisis. On the other hand, it’s the first application of the MSF to aviation policies, allowing it consider the role of other factors besides technical feasibility or European influence in the Government’s decision. The results of this work will be of interest to managers of state-owned airlines and companies, members of government and the wider public policy community.